3D Game Content Distributed Adaptation in Heterogeneous Environments. (17th September 2007) - Morán Morán, Francisco Francisco; Preda Preda, Marius Marius; Lafruit Lafruit, Gauthier Gauthier; Villegas Villegas, Paulo Paulo; Berretty Berretty, Robert-Paul Robert-Paul
Abstract : Most current multiplayer 3D games can only be played on a single dedicated platform (a particular computer, console, or cell phone), requiring specifically designed content and communication over a predefined network. Below we show how, by using signal processing techniques such as multiresolution representation and scalable coding for all the components of a 3D graphics object (geometry, texture, and animation), we enable online dynamic content adaptation, and thus delivery of the same content over heterogeneous networks to terminals with very different profiles, and its rendering on them. We present quantitative results demonstrating how the best displayed quality versus computational complexity versus bandwidth tradeoffs have been achieved, given the distributed resources available over the end-to-end content delivery chain. Additionally, we use state-of-the-art, standardised content representation and compression formats (MPEG-4 AFX, JPEG 2000, XML), enabling deployment over existing infrastructure, while keeping hooks to well-established practices in the game industry.